Eating behavior’s changes in medical students during the Covid-19 (Research, Society and Development, 2023)
The Covid-19 pandemic and the necessary actions to face it were related to a series of psychological and behavioral implications. For medical students, the change in the university’s teaching methodology was another stress factor in a population that already has a higher risk of developing eating disorders. Thus, this study aimed to evaluate changes in medical student’s eating behavior during the Covid-19 pandemic. A cross-sectional, observational study was carried out with medical students in Fortaleza - CE. A total of 182 participants responded to the survey. Of these, 81.3% and 81.8% reported changes in body weight and in eating habits, respectively, during the evaluated period. The most reported behaviors were: cooking more, ordering more food delivery, feeling the need to have more meals, having more episodes of snacking and eating to relieve feelings. Since some of these changes are risk factors for developing an eating disorder, we suggest the need for nutritional and lifestyle counseling, and provision of mental health support for medical students, as a strategy to minimize the risks of developing eating disorders.